LEARNING SCIENCE THROUGH ONLINE SYSTEM: WHATSAPP VS GOOGLE MEET PLATFORM - Meliana Meliana; Muhammad Junus; Nurul Fitriyah Sulaeman (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
During the pandemic of COVID-19, the utilization of online platforms is essential for the learning process. This research aims to determine differences in student learning outcomes using the Whatsapp and Google Meet platforms in distance learning during the Covid-19 pandemic with Energy Material in the Life System of Junior High School Students. The type of research is experimental research. This study's sample was class VII A students totaling 34 students and class VII B students totaling 33 students—data collection using multiple-choice questions to measure student learning outcomes (posttest) and confirmation through interview. The results showed no difference in student learning outcomes using the Whatsapp and Google Meet platforms in distance learning during the Covid-19 pandemic. Students show different engagement through the two platforms.